Effect of capital flight on domestic investment: Evidence from Africa - Fentaw Leykun Fisseha (Cogent Economics & Finance, 2022)
Capital flight is a major issue in developing economies; the problem is more severe in Africa, where domestic investment has been affected. Much attention has been given to the effect of legal and foreign capital flows in the international capital movement, disregarding illicit capital outflows (capital flight) from developing countries including Africa. This study examines the effects of capital flight and financial liberalization on domestic investment using the dynamic system generalized method of moments (GMM) for 30 African nations between 2000 and 2019. The econometric analysis revealed that capital flight is one of the conditions that severely constrains domestic investment financing in Africa. However, the impact of financial liberalization on domestic investment is shown to be insignificant. The empirical evidence is used to draw some policy implications aimed at reducing capital flight and enhancing domestic investment.
Keywords: E22; O16; P33; P45; 330; capital flight; financial liberalization; domestic investment; system GMM; savings